1982
DOI: 10.1021/bi00266a037
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of peptide transport in Saccharomyces cerevisiae

Abstract: Oligopeptides and dipeptides are transported into Saccharomyces cerevisiae by a carrier-mediated system. In the dark, leucyl-p-nitroanilide (Leu-p-NA) and leucyl-leucyl-4-azido-2-nitrophenylalanine [Leu-Leu-Phe-(4N3,2NO2)] are competitive inhibitors of peptide transport by S. cerevisiae cells. The photolysis of yeast cells in the presence of Leu-p-NA or Leu-Leu-Phe(4N3,2NO2) at 350 nm results in an irreversible inactivation of peptide transport. Protection against this inactivation is afforded by an excess of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…When working on peptide transport in Saccharomyces cerevisiae, Jeffrey M. Becker observed that leucyl-p-nitroanilide is a competitive inhibitor of peptide transport and used it as a photoaffinity label for the carrier protein (Becker et al 1982). Daniel & Adibi (1994) found that amino acid 4-nitroanilides are recognized by mammalian renal peptide transporters with high affinity.…”
Section: Amino Acid Derivativesmentioning
confidence: 99%
“…When working on peptide transport in Saccharomyces cerevisiae, Jeffrey M. Becker observed that leucyl-p-nitroanilide is a competitive inhibitor of peptide transport and used it as a photoaffinity label for the carrier protein (Becker et al 1982). Daniel & Adibi (1994) found that amino acid 4-nitroanilides are recognized by mammalian renal peptide transporters with high affinity.…”
Section: Amino Acid Derivativesmentioning
confidence: 99%
“…The polar epimer 27 was obtained as an oil (63 mg, 6%): NMR (acetone-d6) 5.66 (m, 2 H, CH=CH), 4.05 (m, 1 H, C-15 ), 3.90 (q, 1 H, C-ll H). The mobile epimer 28 was obtained as an oil (152 mg, 15%): NMR (acetone-d6) 6 5.66 (m, 2 H, CH=CH), 4.05 (m, 1 H, C-15 H), 3.90 (q, 1 H, C-ll H). In addition fractions consisting of a mixture of the epimers, Rf 0.38 and 0.50 (1% HOAc in EtOAc), were obtained (100 mg, 10%).…”
Section: -[5-oxo-3-[2-[(trimethylsilyl)oxy]ethoxy]-l-cyclopenten-l-yl...mentioning
confidence: 99%
“…Found: 481.3208). " 3.38 (s, 1 H, OH), 1.03 [t,6 H, N(C773CH2)2], kk S: caled, 6.49; found,5.86.Derivatives of 11-Deoxyprostaglandins E¡…”
mentioning
confidence: 99%